2022
DOI: 10.33806/ijaes2000.22.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive Strategies of Saudi EFL Learners

Abstract: The aim of this study is to investigate the speech act of persuasion used by Saudis learning English as a foreign language (EFL). Moreover, we seek to explore the differences between genders in the use of these strategies. The participants are 50 males and 50 females at level 7 of their bachelor’s degree in English. Data are collected using the Discourse Completion Test (DCT) method, which contains six scenarios similar to real-life situations. Data are analysed quantitatively using the Cross-Cultural Speech A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The study implied that male Jordanians boost their male dominance in the Jordanian community by being assertive while female Jordanians tend to focus on their social relations (p. 410). A more recent study by Almegren (2022) investigated gender differences between Saudi males and females in the speech act of persuasion. After carrying out a Discourse Completion Task (DCT), the findings indicated that male Saudis used more direct persuasion strategies (e.g.…”
Section: Language and Gendermentioning
confidence: 99%
“…The study implied that male Jordanians boost their male dominance in the Jordanian community by being assertive while female Jordanians tend to focus on their social relations (p. 410). A more recent study by Almegren (2022) investigated gender differences between Saudi males and females in the speech act of persuasion. After carrying out a Discourse Completion Task (DCT), the findings indicated that male Saudis used more direct persuasion strategies (e.g.…”
Section: Language and Gendermentioning
confidence: 99%